«Care of the self» as a pedagogical concept of the physical education of student youth - Sadovnikov, E.S.; Zhegalova, M.N.; Fantrov, P.P.; Mansuri, Akhmed Akil Murad (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyze in what way the concept of “care of the self” can act as an instrument of the physical education of the student youth of the city of Volgograd, and to substantiate the pedagogical guidelines ensuring the transition from the recognition of the value of health to regular practices of self-preserving behavior. Methods and structure of the study. The article reveals the potential of the concept of “care of the self” as a pedagogical instrument of the physical education of student youth and shows its connection with the stability of everyday practices aimed at strengthening health. The empirical base of the study is represented by the results of a questionnaire survey of 400 students aged 17–30 studying in the educational organizations of the city of Volgograd. Results and conclusions. It was established that the majority of the respondents recognize the care of health and education as socially significant practices influencing the possibility of being useful to society, and at the same time a gap is recorded between the expressiveness of the value attitudes and the regularity of actions. A conclusion is drawn about the pedagogical expediency of designing, in the university environment, an “infrastructure of care of the self,” translating the intentions of students into regular forms of physical-culture and health-improving activity and self-regulation.